AKTIVITAS ANTIFUNGI EKSTRAK DAUN PICUNG TERHADAP CENDAWAN Botryodiplodia theobromae PENYEBAB MATI PUCUK BIBIT JABON MERAH Antifungal Activity of Picung Leaf Extracts Against Botryodiplodia theobromae A Dieback Fungus of Jabon Merah Seedling - L M. Alfin Agushara Bena; Achmad .; Syamsul Falah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Invasion of Botryodiplodia theobromae as a dieback fungus on jabon merah (Anthocephalus macrophyllus) seedlings is a crucial issues. This pathogenic fungus needs to be controlled precisely. Phytochemical compounds of plant material is one alternative fungicides. Crude extracts of picung (Pangium edule) leaf in water and methanol solvent known to have antifungal potential. However, its activity against B. theobromae need to be revealed. In vitro assay aimed to measuring antifungal activity of water and methanol extracts of picung leaf on controlling growth of B. theobromae pathogenic fungus. Hot water extraction and maceration in methanol was conducted to obtain crude extract materials. In-vitro antifungal assay of water and methanol extracts of picung leaf was conducted by food poisoning method on Potato Dextrose Agar media. The results showed that water and methanol extracts of pangi leaf be able to suppress the growth of B. theobromae on the first day of observation, with the highest antifungal index reached 100% at concentration of 25mg/mL and 50mg/mL, respectively. This indicates that water and methanol extracts of picung leaf have antifungal activity. Generally, there was a trend of decrease in antifungal index over time.Key words: antifungal activity, Botryodiplodia theobromae, jabon merah, picung